2016
DOI: 10.1590/s2179-975x0716
|View full text |Cite
|
Sign up to set email alerts
|

Land use effects and stream metabolic rates: a review of ecosystem response

Abstract: Aim To conduct a review of the literature in order to identify the general stream metabolic responses to land use change. Methods I conducted a scientometric review analyzing the distribution of the studies among different environments, the land use scale used, and the general trends in stream metabolism response under each kind of land-use impact. Major Results Most of the analyzed studies were conducted in temperate environments, studying land-use impacts at catchment scale. Ecosystem metabolism responded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…In contrast to the global trend, agricultural streams in our study had lower rates of GPP and ER than their low‐intensity agricultural counterparts. Silva‐Junior () performed a systematic review to evaluate land use effects on stream metabolism worldwide and found that most studies reported increases in GPP and ER rates associated with agriculture. Whereas Gücker et al () found lower rates of ER in agricultural Cerrado streams as a result of increased bottom shear stress that decreased benthic microbial biomass in the central streambed, we did not find significant differences in current velocity between agricultural and low‐intensity agricultural streams in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the global trend, agricultural streams in our study had lower rates of GPP and ER than their low‐intensity agricultural counterparts. Silva‐Junior () performed a systematic review to evaluate land use effects on stream metabolism worldwide and found that most studies reported increases in GPP and ER rates associated with agriculture. Whereas Gücker et al () found lower rates of ER in agricultural Cerrado streams as a result of increased bottom shear stress that decreased benthic microbial biomass in the central streambed, we did not find significant differences in current velocity between agricultural and low‐intensity agricultural streams in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The studied agricultural streams also had lower ratios of transient storage areas to stream channel cross-sectional area (A S /A; Table 2) that may be important predictors of ecosystem function in South American streams (Gücker et al, 2009;Gücker & Boëchat, 2004 In contrast to the global trend, agricultural streams in our study had lower rates of GPP and ER than their low-intensity agricultural counterparts. Silva-Junior (2016) performed a systematic review to evaluate land use effects on stream metabolism worldwide and found that most studies reported increases in GPP and ER rates associated with agriculture. Whereas Gücker et al (2009) found lower rates of ER in agricultural Cerrado streams as a result of increased bottom shear stress that decreased benthic microbial biomass in the central streambed, we did not find significant differences in current velocity between agricultural and low-intensity agricultural streams in the T A B L E 4 Best multiple linear regression models (p < .05 and adjusted R 2 ≥ .60) for the ambient SRP uptake metrics Sw amb and V famb as functions of environmental variables for the low-intensity agricultural and agricultural stream sites in Brazil and Argentina Note.…”
Section: Ecosystem Metabolism and Nutrient Dynamicsmentioning
confidence: 99%